Status of Greenland in the Constitutional and Political System of Denmark: To Be or Not to Be a Sovereign Country? - Stanković, Marko (NBP. Nauka, bezbednosti, policija, 2025)
The article analyses the legal, political, economic and geostrategic aspects of Greenland’s status in the Kingdom of Denmark. After the introductory remarks, there is a brief presentation of the theoretical concept of territorial autonomy, because Greenland is usually considered to be an autonomous territory. It is followed by an overview of the evolution of the status of Greenland in the Kingdom of Denmark. The central part of the paper is the analyses of the legal framework of the current status of Greenland, guaranteed by the Act on Greenland Self-Government of 2009, with particular reference to the system of government, competences, foreign policy and the possibility of gaining independence from Denmark. Next chapter contains the data about political parties in Greenland and recent political dynamics, with special reference to the March 2025 elections, which were marked by the annexation threat by the US President Donald Trump. The concluding remarks summarize the results of the research, especially the legal, political, economic and geostrategic aspects related to the eventual declaration of independence of Greenland.
Keywords: Greenland, Kingdom of Denmark, devolution, autonomy, independence.